Scientific motivations and criteria to consider updating EFSA scientific assessments. (17th March 2017) - ,; Hardy, Anthony; Benford, Diane; Halldorsson, Thorhallur; Jeger, Michael John; Knutsen, Katrine Helle; More, Simon; Mortensen, Alicja; Naegeli, Hanspeter; Noteborn, Hubert; Ockleford, Colin; Ricci, Antonia; et al.
Abstract: EFSA is committed to assess and communicate the risks occurring in the food and feed chain from farm to fork and to provide other forms of scientific advice. This work, carried out by EFSA since its inception, has resulted in the adoption of thousands of scientific assessments. EFSA is obliged to re‐assess past assessments in specific regulatory contexts such as those on food and feed additives, active substances in plant protection products and genetically modified food and feed. In other sectors, the consideration for updating past EFSA scientific assessments is taken on an ad hoc basis mainly depending on specific requests by risk managers or on EFSA self‐tasking. If safety is potentially at stake in any area within EFSA's remit, the readiness to update past scientific assessments is important to keep EFSA at the forefront of science and to promote an effective risk assessment. Although this task might be very complex and resource demanding, it is fundamental to EFSA's mission. The present EFSA Scientific Committee opinion deals with scientific motivations and criteria to contribute to the timely updating of EFSA scientific assessments. It is recognised that the decision for updating should be agreed following careful consideration of all the relevant elements by the EFSA management, in collaboration with risk managers and stakeholders. The present opinion addresses the scientific approaches through which it would be possible for EFSA to increase the speed and effectiveness of the acquisition of new data, as well as, to improve the consequent evaluations to assess the relevance and reliability of new data in the context of contributing to the better definition of whether to update past scientific assessments.